Catalyst-free and wavelength-tuned glycosylation based on excited-state intramolecular proton transfer - Min Hou; Xiaoling Jing; Guoen Wen; Haibing He; Shuanhu Gao (Nature Communications)
Abstract The chemoselectivity of organic reactions is a fundamental topic in organic chemistry. In the long history of chemical synthesis, achieving chemoselectivity is mainly limited to thermodynamic conditions by an exogenous activation strategy. Here, we design an endogenous activation method, which can be used to control the chemoselectivity of phenol and naphthol through the photo-induced excited-state intramolecular proton transfer (ESIPT). A wavelength-tuned glycosylation is developed to showcase the penitential of this new strategy. Traditionally, an exogenous activator (electrophilic promoters) is essential to induce the cleave of a polar single bond, and this strategy has been extensively studied and used in the glycosylation chemistry, for the formation of oxocarbenium cation intermediate. In our systems, the oxocarbenium cation intermediates can be selectively formed from glycosyl donors bearing tunable chromophoric groups under mild conditions of acid-base free and redox neutrality, which enables continuous synthesis of oligosaccharides.